Social change anytime everywhere how to implement online multichannel strategies to spark advocacy, raise money, and engage your community - Kapin, Allyson, 1974- (Jossey-Bass, 2013)
"The nonprofit's how-to guide for using online media to further their missionsThis book is written for nonprofit staff who say themselves or are asked by others, Email communications, social media, and mobile are important, but how will they help our nonprofit and the issues we work on? Most importantly, how the heck do we integrate and utilize these tools successfully? The book will help answer these questions and is organized to guide readers through the planning and implementation of online multi-channel strategies that will spark advocacy, raise money and promote deeper community engagement in order to achieve social change in real time. Offers a practical guide for nonprofits on how to best implement online and social media Outlines the various types of mobile media and online and when it makes sense to use them Shows how to build mobile expertise into the staff structure and sell mobile initiatives to the board Social Change Anytime Everywhereserves as a resource to help nonprofit staff and their boards quickly understand the evolving online landscape and identify and implement the best online channels, strategies, tools, and tactics to help their organizations achieve their missions"--